CLINICAL AND ENCEPHALOGRAPHIC CHANGES AT LENNOX–GASTAUT SYNDROME - K. Yu. Mukhin (Русский журнал детской неврологии)
The Lennox–Gastaut syndrome (LGS) is an epileptic encephalopathy, starting in childhood and showing in often polymorphic seizures (including tonic axial ones), severe cognitive deficite, slow activity of the acute–slow wave in the interictal period at the electroencephalography (EEG), runs of fast activity of 10–20 Hz, often associated with tonic seizures, as well as with the resistance to therapy. According ILAE Classification of epilepsy syndromes and epilepsies 1989 LGS was referred to generalized cryptogenic or symptomatic forms of the epilepsy. According to Proposed Diagnostic Scheme for People with Epileptic Seizures and with Epilepsy (2001) LGS is a classic representative of the group of childhood epileptic encephalopathies. LGS is a rather rare form of the epilepsy. The syndrome frequency makes from 1–4 to 6.6 % among all forms of the childhood epilepsy. LGS is subdivided into the cryptogenic and the symptomatic variants. From our point of view the latter it will be more correct to refer to the symptomatic focal epilepsy with the secondary bilateral synchrony phenomena at EEG. The LGS can be caused by cortical development defects, by perinatal encephalopathies, by brain tumors, by inherited metabolism diseases, by chromosomal anomalies, as well as by other factors. In case of the classic cryptogenic variant the ethiology of the LGS remains unknown. The disease onset is at the age of 2–8 y. o. In 20–40 % of cases LGS is transformed from the West syndrome. The LGS attribute is the polymorphism of seizures. The syndrome structure can combine tonic seizures, epileptic drop seizures, atypical absences, generalized tonic-clonic seizures. Focal seizures at LGS are a matter of argument. The article gives details on the clinical EEG criteria of LGS, the semiology of epileptic seizures in the syndrome structure, diagnostic and treatment approaches. The main accent is made on EEG peculiarities of the disease. The author presents the detailed survey of the modern literature on this matter, as well as the own research data.